2016
DOI: 10.1159/000445076
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation-Induced Transient Nonmotor Psychiatric Symptoms following Subthalamic Deep Brain Stimulation in Patients with Parkinson's Disease: Association with Clinical Outcomes and Neuroanatomical Correlates

Abstract: Background: The clinical and neurobiological underpinnings of transient nonmotor (TNM) psychiatric symptoms during the optimization of stimulation parameters in the course of subthalamic nucleus deep brain stimulation (STN-DBS) remain under intense investigation. Methods: Forty-nine patients with refractory Parkinson's disease underwent bilateral STN-DBS implants and were enrolled in a 24-week prospective, naturalistic follow-up study. Patients who exhibited TNM psychiatric manifestations during DBS parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(55 reference statements)
1
9
1
Order By: Relevance
“…In the other four (04) patients, the active contacts were located in the lateral part of STN which also induced STPS. This is similar to what was reported by Abulseoud and colleagues [ 14 ]. For this reason, we concluded that the side effects of STPS are difficult to avoid by just implanting contacts into dorsolateral STN.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the other four (04) patients, the active contacts were located in the lateral part of STN which also induced STPS. This is similar to what was reported by Abulseoud and colleagues [ 14 ]. For this reason, we concluded that the side effects of STPS are difficult to avoid by just implanting contacts into dorsolateral STN.…”
Section: Discussionsupporting
confidence: 93%
“…(1) In earlier studies, STPS was implicated with stimulation of the medial and inferior part (limbic part) of STN. However, recent studies show their active contacts located in the dorsolateral (sensorimotor) area of STN [ 14 ] which also induces STPS. Because of this reason, the limbic and sensorimotor regions of the STN overlap were greater than what has been previously reported [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have intraoperatively looked for psychotropic effects that might possibly occur [31]. Euphoria, mirthful laughter, confusion, etc., typical psychiatric effects under STN DBS in Parkinson’s disease [32] have not been observed neither during surgical placement of electrodes and test stimulation nor in the context of chronic adjustment of stimulation parameters. We have occasionally seen some unilateral and mild aversive response during test stimulation (patients never mentioned “anxiety” but “aversiveness” on request) on more posterior electrode positions.…”
Section: Methodsmentioning
confidence: 99%
“…The same acute vs. chronic distinction can be made regarding neuropsychiatric symptoms. Some symptoms occur immediately upon STN-DBS onset, such as hypomania, laughing or crying (Krack et al, 2001;Mallet et al, 2007;Wojtecki et al, 2007;Abulseoud et al, 2016), while other symptoms, typically apathy, progressively emerge with chronic stimulation (Drapier et al, 2006;Le Jeune et al, 2009).…”
Section: Acute Vs Chronic Dbsmentioning
confidence: 99%